Neutrophil Gelatinase Associated Lipocalin (NGAL) in Leptospirosis Acute Kidney Injury: A Multicenter Study in Thailand. - Nattachai Srisawat; Kearkiat Praditpornsilpa; Kanitha Patarakul; Malee Techapornrung; Tinnapop Daraswang; Theerapon Sukmark; Kamol Khositrangsikun; Apinya Fakthongyoo; Petchdee Oranrigsupak; Laksamon Praderm; Ummarit Suwattanasilpa; Sadudee Peerapornratana; et al. (PLoS ONE, 2015)
AKI is one of the most serious complications of leptospirosis, an important zoonosis in the tropics. Recently, NGAL, one of the novel AKI biomarkers, is extensively studied in various specific settings such as sepsis, cardiac surgery, and radiocontrast nephropathy. In this multicenter study, we aimed to study the role of NGAL as an early marker and an outcome predictor of leptospirosis associated AKI. Patients who presented with clinical suspiciousness of leptospirosis were prospectively enrolled in 9 centers from August 2012 to November 2014. The first day of enrollment was the first day of clinical suspicious leptospirosis. Blood and urine samples were serially collected on the first three days and day 7 after enrollment. We used three standard techniques (microscopic agglutination test, direct culture, and PCR technique) to confirm the diagnosis of leptospirosis. KDIGO criteria were used for AKI diagnosis. Recovery was defined as alive and not requiring dialysis during hospitalization or maintaining maximum KDIGO stage at hospital discharge. Of the 221 recruited cases, 113 cases were leptospirosis confirmed cases. Thirty seven percent developed AKI. Median uNGAL and pNGAL levels in those developing AKI were significantly higher than in patients not developing AKI [253.8 (631.4) vs 24.1 (49.6) ng/ml, p < 0.001] and [1,030 (802.5) vs 192.0 (209.0) ng/ml, p < 0.001], respectively. uNGAL and pNGAL levels associated with AKI had AUC-ROC of 0.91, and 0.92, respectively. Both of urine NGAL and pNGAL level between AKI-recovery group and AKI-non recovery were comparable. From this multicenter study, uNGAL and pNGAL provided the promising result to be a marker for leptospirosis associated AKI. However, both of them did not show the potential role to be the predictor of renal recovery in this specific setting.